1999
DOI: 10.1108/02652329910305689
|View full text |Cite
|
Sign up to set email alerts
|

Adoption of Internet banking by Australian consumers: an empirical investigation

Abstract: Quantifies the factors affecting the adoption of Internet banking by Australian consumers. The sample for this survey was drawn from individual residents and business firms in Australia. Shows that security concerns and lack of awareness about Internet banking and its benefits stand out as being the obstacles to the adoption of Internet banking in Australia. Suggests some of the ways to address these impediments. Further suggests that delivery of financial services over the Internet should be a part of overall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

38
645
10
27

Year Published

2007
2007
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 741 publications
(720 citation statements)
references
References 12 publications
38
645
10
27
Order By: Relevance
“…According to Polatoglu and Ekin (2001), security comprises of three dimensions -reliability, safety, and privacy. Consumers' concerns about security, which arise from the use of an open public network, have been emphasised as the most important factor inhibiting the adoption and use of IB (Sathye, 1999;Daniel, 1999;Cox and Dale, 2001;Howcroft et al, 2002). Security issues have been identified as significant quality attributes of IB (Liao and Cheung, 2002;Jun and Cai, 2001).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Polatoglu and Ekin (2001), security comprises of three dimensions -reliability, safety, and privacy. Consumers' concerns about security, which arise from the use of an open public network, have been emphasised as the most important factor inhibiting the adoption and use of IB (Sathye, 1999;Daniel, 1999;Cox and Dale, 2001;Howcroft et al, 2002). Security issues have been identified as significant quality attributes of IB (Liao and Cheung, 2002;Jun and Cai, 2001).…”
Section: Methodsmentioning
confidence: 99%
“…Sathye, 1999;Howcroft, Hamilton and Hewer, 2002;Rotchanakitumnuai and Speece, 2003). As the adoption rate of the internet is continuously escalating and as increasingly more people use the internet for their banking actions, it has become increasingly important to pay attention to examining the behaviour of more experienced customers gaining expertise with IB.…”
Section: Introductionmentioning
confidence: 99%
“…It has been recommended by the results of this study that the determinants of service quality provide the basis of customer satisfaction. It has been exposed that while making 5 Polatoglu and Ekin (2001), Eriksson et al, (2005), Musiime and Ramadhan (2011) 6 Sathye (1999), Al Hajri (2008. 7 Jun and Cai (2001), Rod et al, (2009), Nupur (2010 8 Raza and Hanif (2013) enhancements in the satisfaction level of customers, the managers are required to appropriately weight the core performance, features and relative performance factors in context of retail banking.…”
Section: Introductionmentioning
confidence: 99%
“…It is also suggested that managers should concentrate on making amendments in the factors which are not contributing in satisfying the customers in retail banking. Sathye (1999) has conducted a research on adopting the services of online banking in Australia. This study is basically attempted to identify the factors which are averting customers in adoption of internet banking services.…”
Section: Introductionmentioning
confidence: 99%
“…Cunningham, et al, (2004) [28] found that the perceived risk and value would affect the use process of self-service. Security and privacy concerns are the main impediments for the user to decide to use the self-service (Sathye 1999;Howcroft, 2002;Gerrard, 2003;Zhao, 2008;Lee, 2009) [29,33]. Good conditions of facilities affect the usefulness of self-service technology and help to eliminate users' risk perception.…”
Section: Self-servicementioning
confidence: 99%